PEMANFAATAN PARTIKEL TEMPURUNG KEMIRI SEBAGAI BAHAN PENGUAT PADA KOMPOSIT RESIN POLIESTER - Harnowo Supriadi (JURNAL MECHANICAL, 2012)
Abstract The objective of the research is to investigate the effect of composition ratio of polyester as matrix and  Aleurites moluccana  willd  particles on  mechanical properties (hardness,flexure strength and tensile strength) of composite.This experimental research  used  Aleurites moluccana willd  particles as reinforced material and polyester as resin.The instrument for the research were universal testing machine (UTM), hardness testing mac hine. This research had been performed by  making variation of  composition ratio of resin and Aleurites moluccana willd  particles (30 % :70%, 40% :60 %, 50 % : 50% and 60% :40%).The result of this  research show that the maximum hardness of composite was54,1 HRL. The maximum flexure strength was 33,62 N/mm2 and the maximum tensile strength was 16,97 N/mm2. The maximum value of hardness, flexure strength and tensile strength had been  achieved on composition ratio 40 % :60 %.Keywords :  Aleurites moluccana Willd  particles, Aleurites moluccana willd  particles, polyester resin, hardness, flexural strength, tensile strength.